2019
DOI: 10.1039/c9ra03636a
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane ionomers based on amino ethers of ortho-phosphoric acid

Abstract: The etherification of ortho-phosphoric acid with triethanolamine and polyoxypropylene glycol is studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In works, 69,70 polyurethane ionomers (AEPA-PU) based on aminoethers of ortho-phosphoric acid (AEPA) were obtained. It was found that during the preparation of AEPA using triethanolamine as a catalyst and a branching center, a branched compound is formed, in which, due to incomplete ether-ication of H 3 PO 4 with triethanolamine and polyoxypropylene glycol, phosphate anions are present (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In works, 69,70 polyurethane ionomers (AEPA-PU) based on aminoethers of ortho-phosphoric acid (AEPA) were obtained. It was found that during the preparation of AEPA using triethanolamine as a catalyst and a branching center, a branched compound is formed, in which, due to incomplete ether-ication of H 3 PO 4 with triethanolamine and polyoxypropylene glycol, phosphate anions are present (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Transitions due to the destruction of supramolecular formations are not observed in this temperature range for AEPA-PPG-1000-PU obtained at SC = 60 wt.%. Judging by the higher thermal stability of the AEPA-PPG-1000-PU samples obtained at SC = 100 wt.% compared to the AEPA- PPG-1000-PU obtained at SC = 60 wt.%., it can be concluded that the supramolecular structures that break down at 100–130 °C are clusters resulting from the combination of phosphate anions in the AEPA-PPG-1000-PU matrix [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…In [ 40 , 41 ], exhibiting thermosensitive water vapor permeability, porous polyurethane ionomers based on the aminoethers of boric acid were synthesized. In [ 42 , 43 ], polyurethane ionomers (AEPA-PPG-PU) were obtained based on aminoethers of ortho -phosphoric acid (AEPA-PPG). It was found that, during the preparation of AEPA-PPG using triethanolamine as a catalyst and a branching center, a branched compound is formed, in which, due to incomplete etherification of H 3 PO 4 with triethanolamine and polyoxypropylene glycol (PPG), phosphate anions are present and surrounded by protons ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the use of triethylamine (TEA) as a catalyst (Scheme 2) results in the etherification of OPA by polypropylene glycol (PPG), leading to the predominance of polyphosphate structures (EPA). [55][56][57] Polyurethanes (EPA-PU) and polyurethane ionomers (AEPA-PU) based on the EPA and AEPA were obtained using polyisocyanates of an aromatic nature. In Reference 51, it was shown that the features of the chemical structure of AEPA-PU are the cause of the ionogenic phosphate group aggregation in the form of proton-conducting channels (Scheme 3).…”
Section: Introductionmentioning
confidence: 99%
“…In References 55–57, polyurethane ionomers based on the aminoethers of ortho‐phosphoric acid (AEPA) were synthesized. The synthesis of AEPA is based on the etherification reaction of ortho‐phosphoric acid (OPA) in the presence of tertiary amines.…”
Section: Introductionmentioning
confidence: 99%